2017
DOI: 10.1016/j.aogh.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Mortality of Colorectal Cancer and Its Relationship With the Human Development Index in Asia

Abstract: Cancer incidence and mortality are higher in countries with more development. A positive and statistically significant correlation was found between standardized incidence and mortality rate of colorectal cancer and the Human Development Index and its components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Our study herein showed that the incidence of CRC in men was higher than that of women; this is consistent with the results of others [20]. The mean age of patients with CRC in the study area was ~55 years [8], and more serious pattern with rising risk of CRC-related mortality was observed in northwestern neighboring countries (like Turkey, Armenia…) [26]. The results of previous studies in Iran and other countries indicate that CRC in men and women are different in each country and region [8,26,27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study herein showed that the incidence of CRC in men was higher than that of women; this is consistent with the results of others [20]. The mean age of patients with CRC in the study area was ~55 years [8], and more serious pattern with rising risk of CRC-related mortality was observed in northwestern neighboring countries (like Turkey, Armenia…) [26]. The results of previous studies in Iran and other countries indicate that CRC in men and women are different in each country and region [8,26,27].…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of patients with CRC in the study area was ~55 years [8], and more serious pattern with rising risk of CRC-related mortality was observed in northwestern neighboring countries (like Turkey, Armenia…) [26]. The results of previous studies in Iran and other countries indicate that CRC in men and women are different in each country and region [8,26,27]. To our knowledge, it seems likely that deficient in some key trace elements [8] and the microbial flora [28] of the colon at older than 50 could be a significant attributable factor for the development of CRC.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Colorectal cancer (CRC) accounts for 9% of all cancers globally,1 2 making it the second most common cancer in women and the third most common in men 1. Adenocarcinoma that arises from the colonic and rectal epithelium accounts for 90% of CRC cases 3.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic approaches for colorectal cancer are surgery, neoadjuvant radiotherapy (for rectal cancer), and adjuvant chemotherapy (for stage III/IV and high-risk stage II colon cancer) (7). However, the 5-year survival rate for colorectal cancer patients ranges from more than 90% in stage I patients to slightly higher than 10% in stage IV patients (8). Thus, it is pivotal to better understand the biological and immunological mechanism for colorectal cancer progression and clinical relevant insights for management of the disease.…”
Section: Introductionmentioning
confidence: 99%